KAJIAN KRITIS: PENGARUH CAPAIAN PENDIDIKAN PNS TERHADAP EFEKTIVITAS PEMERINTAHAN DAN PERTUMBUHAN EKONOMI - Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
This paper is a critical review of a research conducted by Arezki & Quintyn (2013) in the Finance & Development, IMF. Their research is important because it is a pioneer research linking educational attainment by the civil servants to the effectiveness of government that affects economic growth. The research found the quality of education of civil servant is associated with higher state governing capacity, resulting in better decision, and ultimately better development outcome. As a preliminary study, it provides new insights on the importance of improving the quality of civil servants. In the methodology, this study also presents more appropriate technique for measuring the quality of education. It used as weights a countrywide academic ranking from university where civil servants obtain their degree as proxy of quality of education. This technique is better than computing a weighted average of officials’ years of education. On the other side, the research also have weaknesses, especially in the data and the statistical methodology. The data comes from the IMF training applicants' CV and all of them work in central banks and ministries of economy and finance. Consequently, the data can not represent the entire civil servants in 178 countries studied. The following weakness is the use of correlation methods to see causality. This paper also shows that based on the data of civil servants in Indonesia, it is difficult to conclude these findings can be applied in Indonesia